Enzyme Activities and Growth Abilities: Exploring Wood Decay Fungi in Banyuasin Oil Palm Plantations - Arieny, Mutiara; Nengah Dwianita Kuswytasari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Wood fungi, frequently identified as the cause of Wood Rot Disease, produce enzymes that break down key components of plant cell walls, such as cellulose and lignin, allowing the fungi to act as pathogens. This study aims to identify wood fungi present in oil palm plants in Banyuasin, South Sumatra, and to test their growth abilities on various types of wood and enzyme activites (ligninase, cellulase, and hemicellulase). The research methods consist of isolation using an exploration method, morphological identification, and enzyme activities tests (cellulase, hemicellulase, and ligninase). Wood fungus isolation used Potato Dextrose Agar (PDA) media. Fungal morphology was identified macroscopically and microscopically. The data obtained from fungal morphology observations, fungal growth on wood, and enzyme activity were analyzed descriptively. A total of 11 isolates were obtained. Isolates A6, A7, and A11 showed high enzymatic activity, particularly in breaking down lignin, cellulose, and hemicellulose, which potentially causes BPB in oil palms. The cellulase enzyme activity, measured with CMC substrate, indicated that isolate A6 had the highest value (157.30 U/mL), followed by A8 (151.75 U/mL), while A10 had the lowest value (20.58 U/mL). Using Avicel substrate to measure hemicellulase, isolate A10 showed the highest value (108.67 U/mL). For ligninase measured with tannin substrate, isolate A4 had the highest activity (59.89 U/mL), and A10 had the lowest (2.42 U/mL).